Stewardship of digital language archives: training development and testing through collaboration of information scientists, linguists, and communities - Oksana L. Zavalina; Alexandra O'Neil; Shobhana L. Chelliah (Information Research: An International Electronic Journal)
Introduction. Specialized repositories aggregating digital data that focus on languages (of indigenous groups, refugees, etc.) are known as digital language archives (DLA). DLA rapid growth is galvanized by language documentation efforts supported by funding agencies. Recent studies examine DLA user needs and explore support of these needs in digital repositories. Training of LAM professionals in curating and managing DLA to support user needs is emerging, with no research yet into its effectiveness.